Learning Management Based on Blended Learning - Istiqomah, Nurul; Susanti, Astri Febry (Universitas Pendidikan Indonesia (UPI), 2022)
The aims of this research are to: 1) determine the lesson plan,2) organize learning, 3) implement learning, and 4) evaluate the applied learning. This research was conducted at Madrasah Ibtidaiyah Al Falahiyyah, South Jakarta in the academic year 2021/2022. Researchers used a qualitative approach, with a case study method. The research subjects were the principal, teachers, students and guardians of students. Collecting data using interview techniques and documentation studies. Data analysis was carried out by using data analysis techniques, data reduction, data presentation, data verification and drawing conclusions. The results of this study found that the steps in the planning stage include: a) Dissemination of technical instructions from the education office with guardians of students, b) parents and schools form an agreement, c) coordination between schools and relevant government agencies, d) government agencies verify e) the school prepares all kinds of letters needed related to permits to implement PTMT, f) issuance of permits, and g) Implementation of PTMT. School activities consist of annual activities, namely commemorating Islamic and national holidays, monthly activities, namely recitation of guardians of students and weekly activities, namely training on learning methods for teachers which are carried out 2 times a week. The evaluation stage is carried out by involving parents, especially in attitude assessment.